Scanning thermal microscopy techniques for polymeric thin films using temperature contrast mode to measure thermal diffusivity and a novel approach in conductivity contrast mode to the mapping of thermally conductive particles. (February 2015) - Dawson, Angela; Rides, Martin; Maxwell, Antony S.; Cuenat, Alexandre; Samano, Anthony R.
Abstract: Advances in production are leading to increasing use of polymeric thin films in applications such as automotive bearings. Two approaches have been developed to study the thermophysical properties of these thin films: The first technique based on Flash theory uses a scanning thermal microscopy (SThM) tip in temperature contrast mode to measure thermal diffusivity over a nano-scale area. The SThM tip is in contact with the upper surface of the film to detect a heat pulse delivered by a microelectromechanical heater platform from the lower surface. The second technique is a conductivity contrast mode SThM based approach for measuring the size and distribution of thermally conducting particles in thin film polymeric coatings. Topographical and thermal conductivity data are combined to produce a "correlation analysis value" 3D particle map of the coating. Good practice and a case study are highlighted.